The Effectiveness of Honey Purity Testing from Several Regions in Central Sulawesi Province - I Made Budiarsa; Manap Trianto; Akram Akram; Yulia Windarsih; Abdul Ashari (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2025)
Honey is a valuable natural product with nutritional, medicinal, and economic importance, but its high commercial value makes it prone to adulteration, which threatens consumer trust and product quality. This study aimed to evaluate the effectiveness of simple purity tests in identifying adulteration in honey samples collected from several regions in Central Sulawesi Province. A total of 12 honey samples from different bee species and floral sources were analyzed using seven tests, namely solubility, cloudiness and foam, heating, hexagonal pattern, seepage, raw fish, and onion tests. The results showed that most tests successfully distinguished pure honey from adulterated samples. Specifically, the solubility, cloudiness and foam tests, as well as heating, and raw fish tests indicated that 66.67% of the samples were pure, while the hexagonal pattern, seepage, and onion tests confirmed purity in all samples (100%). These findings demonstrate that simple, low-cost methods can provide reliable initial screening of honey purity and are suitable for routine use in local communities where advanced laboratory facilities are limited. The application of these tests is expected to support honey quality assurance, protect consumer trust, and promote the sustainable development of the beekeeping industry in Central Sulawesi.